Pengembangan Multimedia Interaktif Berbasis Android Pada Materi Kimia Sistem Koloid - Sri Setiawaty; Riska Imanda; Ayu Rahmi; Isna Rezkia Lukman; Adevia Ramadhani (Postgraduate, University of Mataram, 2023)
This study aims to produce android-based interactive multimedia on colloidal system chemistry material in high school that is suitable for use, as well as to find out student responses regarding the development of android-based interactive multimedia on colloid system material in high school. The method used in this study is research and development (Research and Development) 4D model (Define, Design, Develop and Disseminate). In this case, researchers only carry out research from up to stage three (Develop). The subjects used were 20 students who were taken randomly. The research instruments used included validation sheets, feasibility questionnaires, and student response questionnaires. The validation results by experts show that the developed interactive multimedia is feasible to use with an average validation score of material experts reaching 84.57%, media experts 90.83%, eligibility by educators 90.37% and student responses of 89.53% . The results obtained from the validators, educators, and students indicate that this interactive multimedia is feasible for use in colloidal chemistry learning.